The epileptic cat and family resilience - Modesto, Antônio Augusto Dall'Agnol; Aragão, Cristal Oliveira Moniz de (Medicina Veterinária, 2020)
Pets have become members of the families who adopt them, and the illness of a family member is known to impact the life of the family. Epilepsy is less common in cats than in dogs but is one of the major neurological manifestations in these animals and may be a model for discussing the impacts that chronic illness of a domestic animal brings to the family. The objective of this paper is to discuss family resilience – the ability of the family to adapt to cope with crises – from the case report of a cat with epilepsy, cared for by the authors, a family physician and a social psychologist. This experience inspired them to bring to the veterinary field some concepts and devices from their areas of knowledge. After an exposition of the clinical case and the feelings aroused in the couple, elements of illness in a family and the domains of family resilience to be considered in the care of animals with chronic diseases (belief system, organizational patterns and communication capacity) are discussed, and some interventions that can be applied in veterinary care are indicated. This exchange of knowledge will help caregivers and veterinarians have a better experience when handling chronic illness, as they deal with its family impacts more properly and hopefully.